Experiencing intercultural communication : - Martin, Judith N. (McGraw-Hill Higher Education, 2013)
Through understanding the complexities of intercultural interaction, students begin the process of learning about other cultures in their professional endeavors and personal relationships. This book provides students with a framework to begin building their intercultural communication skills.